Improving the sensory and nutritional quality of fresh meat - Kerry, Joseph (Microbiologist); Ledward, David (Woodhead Pub. ; CRC Press, 2009)
Understanding of the scientific basis of quality attributes in meat is becoming more advanced, providing more effective approaches to the control of meat eating and technological quality. This important collection reviews essential knowledge of the mechanisms underlying quality characteristics and methods to improve meat sensory and nutritional quality. Part one analyses the scientific basis of meat quality attributes, such as texture and tenderness, colour, water-holding capacity and flavour development. Chapters on the nutritional quality of meat and meat sensory evaluation complete the section. Part two discusses significant insights into the biology of meat quality obtained from genomic and proteomic perspectives, with chapters focussing on different types of meat. Parts three and four then review production and processing strategies to optimise meat quality, considering aspects such as production practices and meat nutritional quality, dietary antioxidants and antimicrobials, carcass interventions, chilling and freezing and packaging. Methods of meat grading and quality analysis are also included. With its distinguished editors and international team of contributors, Improving the sensory and nutritional quality of fresh meat is a standard reference for those industrialists and academics interested in optimising meat quality. Reviews methods to improve meat sensory and nutritional quality considering the effects of different production practices such as chilling, freezing and packagingAnalyses the scientific basis of meat quality attributes covering texture, tenderness, colour and water-holding capacityExamines production and processing strategies to optimise meat quality, including the current state of development and future potential.
Keywords: Meat -- Quality.; Meat industry and trade -- Quality control.; elektronické knihy; electronic books